Magma fracking and production reservoirs beneath and adjacent to Mutnovsky volcano based on seismic data and hydrothermal activity - Kiryukhin A.V.; Polyakov A.Y.; Voronin P.O.; Zhuravlev N.B.; Usacheva O.O.; Solomatin A.V.; Kiryukhin P.A. (My University, 2022)
Mutnovsky geothermal area in Kamchatka, Russia where 62 MWe GeoPP installed - is a source of geothermal electricity supply, as well as a hazard volcanic area. We used local seismicity micro-earthquakes (MEQ’s) data from 2009 to 2021 to define seismogenic faults beneath and adjacent to Mutnovsky volcano, which interpreted as magma injections in form of dykes and sills. Magma fracking beneath Mutnovsky volcano pointed on shear mode low angle dykes in northeast sector and opening mode geomechanical conditions at -3000 m, where sills in area of 62 km2 are suggested to be formed. Low angle dykes injections were reproduced by hydromechanical simulation using CFRAC, modeling results matches with MEQ’s statistics observed. Mutnovsky GeoPP steam collection system shows sensitivity to non-condensable gasses (NCG) content (partial gas pressure) variations (2019—2020), that is used as indicator of magmatic gasses recharge via magma fracking volcano system to production geothermal reservoir. Partial gas pressure measured at GeoPP condenser unit. Magma injections associated with NCG (CO2) release in production reservoirs seems to be synchronize with partial NCG pressure excursions at GeoPP condenser. Some signs of magma fracking events were also revealed using discreet observations (2016–2021) on a blowing wells on a foothills of Mutnovsky volcano. Magma fracking beneath Mutnovsky volcano is associate with small and medium hydrothermal explosions and landslide (2009–2021). Magma fracking distributions pointed on a new potentially production geothermal reservoir beneath northeast foothills of Mutnovsky volcano (depth range from -4000 to -2000 m, accessible area of 30 km2).
Keywords: 38.19.17 Землетрясения и сейсмотектоника; 38.61.15 Динамика и режим подземных вод; 38.61.19 Минеральные, термальные воды и рассолы; 38.61.31 Ресурсы подземных вод; Мутновский